Prodigies [large type] - Armstrong, Bob, 1960- (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"Prodigies focuses on three youths with uncanny abilities who converge on Deadwood in the late 1870s. The issues of the day -- the collapse of Reconstruction, the economic depression of the 1870s, the slow rise of the union movement, the growing power of the robber barons, rapid immigration, and the beginnings of mass culture -- shape the lives of Daniel McCormack, Josiah Stuart, and Lily Mandevillle."--Back cover.